Ponatinib efficacy and safety in Philadelphia chromosome–positive leukemia: final 5-year results of the phase 2 PACE trial - Cortes, Jorge E.; Kim, Dong-Wook; Pinilla-Ibarz, Javier; le Coutre, Philipp D.; Paquette, Ronald; Chuah, Charles; Nicolini, Franck E.; Apperley, Jane F.; Khoury, H. Jean; Talpaz, Moshe; DeAngelo, Daniel J.; Abruzzese, Elisabetta; et al. (Blood, 2018)
Ponatinib has potent activity against native and mutant BCR-ABL1, including BCR-ABL1T315I. The pivotal phase 2 Ponatinib Ph+ ALL and CML Evaluation (PACE) trial evaluated efficacy and safety of ponatinib at a starting dose of 45 mg once daily in 449 patients with chronic myeloid leukemia (CML) or Philadelphia chromosome–positive acute lymphoblastic leukemia (ALL) resistant/intolerant to dasatinib or nilotinib, or with BCR-ABL1T315I. This analysis focuses on chronic-phase CML (CP-CML) patients (n = 270) with 56.8-month median follow-up. Among 267 evaluable patients, 60%, 40%, and 24% achieved major cytogenetic response (MCyR), major molecular response (MMR), and 4.5-log molecular response, respectively. The probability of maintaining MCyR for 5 years was 82% among responders. Dose reductions were implemented in October 2013 to decrease the risk of arterial occlusive events (AOEs); ≥90% of CP-CML patients who had achieved MCyR or MMR maintained response 40 months after elective dose reductions. Estimated 5-year overall survival was 73%. In CP-CML patients, the most common treatment-emergent adverse events were rash (47%), abdominal pain (46%), thrombocytopenia (46%), headache (43%), dry skin (42%), and constipation (41%). The cumulative incidence of AOEs in CP-CML patients increased over time to 31%, while the exposure-adjusted incidence of new AOEs (15.8 and 4.9 per 100 patient-years in years 1 and 5, respectively) did not increase over time. These final PACE results demonstrate ponatinib provides durable and clinically meaningful responses, irrespective of dose reductions, in this population of heavily pretreated CP-CML patients. This trial was registered at www.clinicaltrials.gov as #NCT01207440. •Ponatinib continued to provide deep, durable responses in heavily pretreated patients with CP-CML.•Tolerability was acceptable in this heavily pretreated population with 5 years of follow-up. [Display omitted]